2021
DOI: 10.1002/msc.1543
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study using video analysis of rheumatology specialist nurses conducting methotrexate education consultations with patients

Abstract: Background: Prior to commencing methotrexate, patients routinely attend an education consultation with a rheumatology nurse. The purpose of the consultation is to discuss the patients' expectations and concerns related to commencing methotrexate, the benefits of treatment, potential side effects and monitoring requirements. The aim of this study was to use video analysis to assess the structure, content and mode of delivery of the consultation. Methods: Video recordings of 10 patient-nurse consultations, invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The education and training of nurses were also studied as this is an important topic for ensuring that patients receive the best possible care (Robinson, 2021;Robinson et al, 2017Robinson et al, , 2018Vlieland et al, 2016). A study conducted in the UK found that most nurses lacked knowledge and confidence in managing patients taking MTX (Robinson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The education and training of nurses were also studied as this is an important topic for ensuring that patients receive the best possible care (Robinson, 2021;Robinson et al, 2017Robinson et al, , 2018Vlieland et al, 2016). A study conducted in the UK found that most nurses lacked knowledge and confidence in managing patients taking MTX (Robinson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies, mostly from the United Kingdom (UK), indicate that the training received by nurses to educate patients to start MTX is very varied, influencing nurses' confidence and competencies (Robinson, 2021; Robinson, Adams, et al., 2021). Confidence came with experience, took many months to develop, and standard training was seen as helpful (Robinson et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation